Usia, Masa Kerja Dan Keluhan Nyeri Punggung Bawah Pada Buruh Pabrik Tahu - Firsty Jovial Noli; Oksfriani Jufri Sumampouw; Budi Tamardy Ratag (Universitas Sam Ratulangi, 2021)
Background: Complaints of low back pain were one of the problems in occupational health. A complaint of low back pain indicates that something is wrong at work. Complaints of low back pain were influenced by many factors such as age and length of work. The purpose of this study is to describe the age, lenght of work and complaints of low back pain in tofu factory workers in the Batukota village, Malalayang district, Manado city. Method: This research is a descriptive study which was conducted in the Batukota sub-district, Malalayang district, Manado city from November 2020 to January 2021. Respondents of this study were 32 tofu factory workers. The variables in this study were age, length of work and complaints of low back pain. The instruments used were questionnaires, cameras, and writing instruments. Data analysis was carried out by univariate. Results: The results was showed that the majority of respondents were in the 21-30 year age group as many as 13 respondents (40.6%) and the least number in the> 40 years group was 3 respondents (9.4%). Furthermore, based on the length of service of the respondents, most of them worked 1-5 years as many as 26 respondents (81.3%). Most respondents were categorized as poor NPB complaints as many as 17 respondents (53.1%). The less good NPB category means that the respondents feel more pain frequently and always in the lower back while working. Conclusion: This research was conclude that most tofu factory workers are aged 21-30 years, working period 1-5 years and complaints of poor NPB. Therefore, it is necessary to carry out further health checks regarding low back pain in tofu factory workers.